ANALYSIS OF FINANCIAL ACCOUNTABILITY TOWARDS PERFORMANCE ACCOUNTABILITY THROUGH THE INTERNAL CONTROL SYSTEM AT MANGGARAI REGENCY GOVERNMENT - Aloisius Hama; Akhsyim Afandi; Jaka Sriyana; Mersiana Varia Juita (Finance : International Journal of Management Finance, 2025)
This study aims to examine the extent to which Financial Accountability influences Performance Accountability with the mediating role of the Internal Control System in the Government of Manggarai Regency. The population in this study consisted of 45 employees working within the Manggarai Regency Government. Sampling was conducted using a census method. Thus, the entire population was taken as the sample, consisting of 45 employees who had worked for more than one year. The data obtained was analyzed using the Partial Least Squares (PLS) approach with the assistance of SmartPLS 3.0 software. The analysis results indicate a significant influence of several variables on Performance Accountability. First, Financial Accountability was proven to have a substantial effect on the Internal Control System. Second, the Internal Control System has a significant relationship with Performance Accountability. Third, Financial Accountability also significantly affects Performance Accountability through the mediating role of the Internal Control System in the Manggarai Regency Government.